Analisis Perbandingan Efektifitas Metode Marker dan Markerless Tracking pada Objek Augmented Reality - Budi Arifitama; Ade Syahputra; Ketut Bayu Yogha Bintoro (JURNAL INTEGRASI, 2022)
Markers in augmented reality is an important component for the emergence of an augmented reality object. The function of the marker is to mark the location of an augmented reality object. Currently, there are two types of markers used in the development of augmented reality, namely marker-based tracking and markerless-based tracking. Marker-based tracking has a marker with a pattern on a printed media. Meanwhile, Markerless-based tracking has a point distribution pattern based on a flat surface. Unfortunately, several previous studies that developed AR applications did not have information on the effectiveness and accuracy between the two methods. It is very important to measure the accuracy of the appearance of AR objects to determine the appearance of AR objects, failing to choose the marker used will cause instability in the appearance of AR objects. This study tested the two markers which is distance, height and angle as a parameter. The results of the test stated that markerless tracking was superior to distances of 150 cm with an accuracy rate of 93% while marker-based tracking was only 83.3%.